KEBIJAKAN PEMERINTAH DAERAH KOTA SURABAYA DALAM RANGKA PEMENUHAN KESEJAHTERAAN WARGA MASYARAKAT DITENGAH PANDEMIK COVID -19 - Pramita sari; Andiani Oktavia Safitri; Unggul Satato; Muda Dzikrillah Haq (Fakultas Hukum Universitas Narotama, 2021)
The Covid-19 pandemic has changed the whole structure of community and state life and has the potential to disrupt the stability of government administration and the general interests of the people in the region. This condition must be immediately addressed by each local government by adopting an epective legal policy oriented to the protection and fulfillment of the rights of citizens. PRIVATE THE PROBLEM The Surabaya City Government has established a Large-Scale Social Restrictions Policy (PSBB) in the context of handling the spread of the Covid-19 pandemic. But on one side does the policy meet the welfare of the citizens? This legal research aims to examine the legal policies of the City Government of Surabaya in the context of handling the spread of the Covid-19 pandemic and the fulfillment of the welfare of the citizens of Surabaya amid the Covid-19 pandemic. Keywords: Covid-19, REGIONAL GOVERNMENT OF SURABAYA CITY, Community welfare